Case Report of Two Patients With COVID-19 and Sacral Pressure Injuries Associated with Pyoderma Gangrenosum. (August 2021) - Elkhatib, Rania; Giunta, Gabriele; Hanssens, Valerie; Kapila, Ayush; De Baerdemaeker, Randy; Zeltzer, Assaf; Hamdi, Moustapha
Abstract : ABSTRACT: During the COVID-19 pandemic, an increasing number of patients have been admitted to the ICU with severe respiratory complications requiring prolonged supine positioning. Recently, many case reports have been published regarding dermatologic manifestations associated with COVID-19. However, there is little information about the clinical features of these manifestations. Pyoderma gangrenosum (PG) is an ulcerative noninfectious inflammatory disease of the skin. In at least 50% of the cases, the etiology is unknown. Nevertheless, PG is associated with many systemic diseases. In this article, the authors report two critically ill patients with COVID-19 who developed sacral ulcers during their recovery in the ICU. These ulcers had an atypical course and were exacerbated by surgical debridements. Accordingly, providers suspected PG, which was confirmed by the clinical evolution of the ulcers and biopsies taken from the wounds. To the best of the authors' knowledge, no previous articles have reported sacral pressure injuries associated with PG in patients with COVID-19. Providers should suspect PG in patients with COVID-19 who develop nonhealing pressure injuries.